Decreasing of Cayenne Pepper Quality During Storage in Room Temperature - Sulistyaningrum, Anna; Darudryo, Darudryo (JURNAL AGRONIDA, 2019)
Cayenne pepper storage at room temperature will cause physical, mechanical, chemical or microbiological damage in short time. In room terperature conditions cayenne pepper can only survive for 2-3 days and finally will be decay. The use of packaging can increase the small chilli storeability, because packaging can reduce the level of exposure to environmental changes. This research aims to study the quality changes of cayenne pepper during storage on room temperature. The results showed that losses of cayenne pepper weight increased with increasing duration of storage. Cayenne pepper storaged for 8 days caused weight loss of 24.25%. The use of perforated plastic packaging can reduce the weight loss by 16.82%, much lower than the control of 31.67%. The pH of chili during the 8-days decreased with value of 6.55 while the control was 6.7. The pH experienced decreased of 2.23% from the control (without packaged). While the number of colored cayenne pepper increased during storage from 40% in control treatment and 60% in the packaging. The use of perforated plastic packaging provides a higher organoleptic value with a total value of 18 which consists of 4.27 color parameters (close to green), texture 4.5 (very close to very hard), 4.6 appearance (near very smooth) and freshness 4.63 (approached very fresh). Keywords: chili, storage duration, weight loss, pH, packing